The Treatment of Recurrent Urothelial Tumors of the Upper Urinary System and at Urostomy Site following Radical Cystectomy with Intraureteral Bacillus Calmette-Guérin and Cryotherapy - Abdullah Demirtaş; Yunus Emre Yıldırım; Ayten Ferahbaş; Emre Can Akınsal; Oguz Ekmekçioğlu; Atila Tatlışen (Case Reports in Urology)
Urinary bladder carcinoma is the second most common cancer of the urinary system. The recurrence rate in the upper urinary system (UUS) for urothelial cancers is around 3% following radical cystectomy. The followup generally consists of imaging studies and urinary cytology, although there are no prospective data on the frequency, the mode, and the duration of followup. In patients carefully selected according to risk factors, kidney-sparing minimally invasive methods (ureteroscopic procedures, percutaneous approach, and local drug instillation) appear as contemporary alternatives for low-grade and low-stage primary UUS. In this paper, we present the patient who underwent radical cystectomy with urinary diversion ureterocutaneostomy, was diagnosed with widespread bilateral UUS tumors and recurrent tumor at the urostomy site at active followup, for which he was given local Bacillus Calmette-Guérin (BCG) and cryotherapy, and was followed by disease-free for 2 years thereafter.